Analisis Variabel Sosial Ekonomi Terhadap Kemiskinan di Indonesia - Dinar Melani Hutajulu; Yustirania Septiani; Jesika Melina Simamora (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
Indonesia's poverty condition in March 2019 recorded at 9.41 percent. Supposedly, Indonesia reaches the RPJMN target where the poverty level is planned at a 7-8 percent level. The High levels of rural poverty compared to urban areas exceeded the percentage of national poverty. Low wages are also an indication that the problem of poverty occurs continuously. The purpose of this research is to know how socio-economic variables such as human development, unemployment, wage, and inequality can affect poverty reduction in Indonesia. This research uses secondary data obtained from the website of Statistics Indonesia (BPS) and the Databoks Katadata website. This study uses cross-section data with 34 provincial observations in the year 2019. This research used econometric methodologies with the regression of Ordinary Least Square as an analysis tool. This research show that poverty in Indonesia is still very dominant in the island of Papua, in the provinces of Papua and West Papua and in the island of Nusa Tenggara, in the provinces of West Nusa Tenggara and East Nusa Tenggara. Human development has a negative effect where every human development increase by 1 percent will reduce poverty in Indonesia by 5.69 percent. The declining unemployment rate has contributed to poverty reduction in Indonesia by 0.34 percent. Wages, in this case, can reduce poverty. Increasing wages by 1 percent can reduce poverty by 1.08 percent and vice versa. Reducing inequality by 1 percent can reduce poverty by up to 1.88 percent.Keywords: poverty, HDI, unemployment, wage, inequality